ANALYSİS OF TURKİSH WOMEN'S COOPERATİVES' USE OF NEW MEDİA - Gülfiz Ergin Demirdağ; Enver Aydoğan; Nurettin Parıltı (PEOPLE: International Journal of Social Sciences, 2025)
The women's cooperative movement in Turkey started in the early 2000s with the aim of preventing women's poverty, valuing women's labour and empowering women. Today, there are five different types of women's cooperatives operating across Turkey. This study analyses the social media use of five different types of women's cooperatives and examines their corporate identity based on the list of women's cooperatives (N = 442) on the website of Simurg Women's Cooperatives Union (SIMURG), one of the women's cooperative unions. Five women's cooperatives were randomly selected from each of the four categories (see Women Environmental, Cultural and Business Cooperative, Women Production and Enterprise Cooperative, Women Production and Marketing Cooperative, Development Production and Marketing Cooperative and Agricultural Development Cooperative) and n=2 cooperatives under the Education, Culture, Solidarity and Enterprise category and the analyses were conducted by examining a total of n=22 women's cooperatives. Case study technique, one of the qualitative research methods, was adopted in the study and document analysis method was used to collect data. The names of the cooperatives were entered into a search engine and their Instagram accounts and websites, if any, were subjected to descriptive analysis according to the criteria set (number of follower, number of posts, logo use, type of the website etc.). According to the findings of the study, it was found that a large number of searches were required to identify the corporate identity of women's cooperatives (areas of activity, where and when they were established, sales channels, etc.). It can be said that women's cooperatives are generally engaged in food production (tomato paste, noodles, jam, olives, etc.) and that the products are an extension of women's domestic work. On the other hand, it was found that women's co-operatives mostly use Instagram to promote their products, share their activities, and announce the events they participate in or organise. While all cooperatives have Instagram accounts, only 9 have websites, of which only 3 are corporate e-commerce websites. Finally, it was found that women's co-operatives do not use social media actively enough, the number of posts is low, and the images shared are unprofessional.